KAJIAN MODEL KESUKSESAN SISTEM INFORMASI DeLONE &McLEAN PADA wifi.id DI KOTAMADYA SUKABUMI - Renny Oktapiani; Dwiza Riana (Swabumi, 2016)
The use of Internet technology today has become a very important requirement and even support allthe activities of our daily work, saah them is the emergence of a new program offered by TelkomIndonesia: Indonesia Wireless Fidelity (wifi.id). This service has been used by the entire territory ofIndonesia which has given Access Point is no exception Sukabumi area. Hence it is important to knowhow the effectiveness of its use in the community. The model is used to look into the matter is referredto the model of success that DeLone & McLean in which there are several factors that InformationQuality, System Quality, Quality of Service, intensity of use, satisfaction Usage and Net Benefits, withdata processing methods SEM (Structure Equation modeling) and using AMOS 21.0 software. Fromthis study proved the quality of service affects the intensity of the user , the intensity of use satisfactionaffect users , and user satisfaction affects the net benefitsKeywords: Methods DeLone & McLean, wifi.id, SEM.